Demonstration and scaling of integrated management of parasitic weeds on faba bean in Northern Ethiopia - Kassaw, Admasie; Assaye, Gebremariam; Abathun, Tamir; Esmael, Jemal; Mihiretie, Aderajew; Mengi, Yechale; Alem, Cherinet; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Parasitic weeds (Orobanche and Phelipanche spp) are key production challenges in the northern parts of Ethiopia. In addition to parasitic weeds, faba bean gall disease is doubling the challenge on faba bean. Besides the reduction in yield, the two non-endemic pests are threatening the genetic diversity of food legumes since the landraces are highly susceptible. This report covers activities conducted in the 2021/22 cropping season